Isotocin neuronal phenotypes differ among social systems in cichlid fishes. Issue 5 (17th May 2017) - Reddon, Adam R.; O'Connor, Constance M.; Nesjan, Erin; Cameron, Jason; Hellmann, Jennifer K.; Ligocki, Isaac Y.; Marsh-Rollo, Susan E.; Hamilton, Ian M.; Wylie, Douglas R.; Hurd, Peter L.; Balshine, Sigal
Abstract : Social living has evolved numerous times across a diverse array of animal taxa. An open question is how the transition to a social lifestyle has shaped, and been shaped by, the underlying neurohormonal machinery of social behaviour. The nonapeptide neurohormones, implicated in the regulation of social behaviours, are prime candidates for the neuroendocrine substrates of social evolution. Here, we examined the brains of eight cichlid fish species with divergent social systems, comparing the number and size of preoptic neurons that express the nonapeptides isotocin and vasotocin. While controlling for the influence of phylogeny and body size, we found that the highly social cooperatively breeding species ( n  = 4) had fewer parvocellular isotocin neurons than the less social independently breeding species ( n  = 4), suggesting that the evolutionary transition to group living and cooperative breeding was associated with a reduction in the number of these neurons. In a complementary analysis, we found that the size and number of isotocin neurons significantly differentiated the cooperatively breeding from the independently breeding species. Our results suggest that isotocin is related to sociality in cichlids and may provide a mechanistic substrate for the evolution of sociality.